3D printing design : additive manufacturing and the materials revolution - Bitonti, Francis, 1983- (Bloomsbury Visual Arts, 2019)
To work with the materials of tomorrow, design students across visual arts disciplines need to understand the cutting edge of today. Whether you're modelling in interiors, designing in fashion or constructing for interiors, in your work or as part of a final project, 3D Printing design is an encouraging guide to additive manufacturing within design disciplines. Francis Bitonti gives an insider's view from his design studio on how 3D printing is already shaking up the industry, and where it's likely to go next. Complete with interviews from designers, business owners and 3D-print experts throughout, Bitonti considers whether 3D body scans mean couture for all, how rapid prototyping can change your design method and if 3D printing materials can enhance medical design, amongst other areas of this emerging method of manufacture. This is inspirational reading for the designers of tomorrow.
Introduction1. The materials revolution of 3D printing2. The future of materials3. Disruptive distribution 4. Case studiesConclusion.
Keywords: Printing, Three-Dimensional.; Three-dimensional printing.; Three-dimensional printing -- Materials.; Design.; Textile industry.; Industrial design.; elektronické knihy; electronic books